The effect of vitamin E incorporated into injectable platelet-rich fibrin on orthodontic tooth movement in rabbits: Vitamin E and injectable platelet-rich fibrin on tooth movement - Mohsin, Mahmoud Kanan; Qadir Omer, Zana (Cellular and Molecular Biology, 2024)
To evaluate the effects of injectable platelet fibrin (iPRF) and combined vitamin E-iPRF on orthodontic tooth movement (OTM) rates in rabbits, 35 male New Zealand white rabbits were involved in this study using splitmouth design. OTM was carried out on the mandibular first premolar using 100g nickel titanium closing coil. Right side served as study group, isolated iPRF in one group and combined vitamin E-iPRF in other group was injected buccally and lingually (iPRF group, Vit E-iPRF group), and left side acted as positive control group (CG) by injecting normal saline (positive CG). The rate of OTM was measured using intra-oral scanner on days 7,14 and 21. Histological and Micro CT scan were examined on days 0, 7, 14 and 21. The iPRF and combined Vitamin E-iPRF demonstrated significant greater rate of OTM on days 7 and 14 in comparison to control group, only significant differences between iPRF and combined vitamin E-iPRF were seen on day 14. In all time intervals as compared to the CG, the number of osteoclasts was significantly higher in the isolated iPRF and combined vitamin E-iPRF groups. Significant reduction in bone volume fraction (BV/TV) was demonstrated in iPRF and combined vitamin E-iPRF groups in all time points, however, non-significant differences were found in trabecular thickness (Tb.Th) and trabecullar separation (Tb.Sp). Local injection of iPRF and combined vitamin E-iPRF showed temporary increase in the rate of OTM.